2017
DOI: 10.1039/c7cp03863a
|View full text |Cite
|
Sign up to set email alerts
|

Structure and molecular packing in smectic BCr and Ad phases of Schiff base liquid crystal compounds through the analyses of layer spacing, entropy and crystal structure

Abstract: Single-crystal structural analyses and heat capacity measurements were performed on two Schiff base liquid crystal compounds, 5CBAA (4-chlorobenzylidene-4'-pentyloxyaniline) and 5ABCA (4-pentyloxybenzylidene-4'-chloroaniline). The alkyloxy-chain of a 5CBAA molecule was conformationally ordered in the crystal at room temperature. While that of 5ABCA was partially disordered in the room temperature phase but ordered in a low-temperature phase at 100 K. The structural phase transition involving the disordering of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…The stereo configurations of the central naphthalene moiety and terminal polar groups played an important role in the predicted thermal parameters, which will be discussed in the computational section. Moreover, the thermal cis/trans isomerization of the azo group was an essential factor in the lower entropy changes observed, as documented in previous studies [ 65 , 69 , 70 , 71 ]. Moreover, due to their nematic nature, of the mesophase, they exhibited the lowest order mesophase.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…The stereo configurations of the central naphthalene moiety and terminal polar groups played an important role in the predicted thermal parameters, which will be discussed in the computational section. Moreover, the thermal cis/trans isomerization of the azo group was an essential factor in the lower entropy changes observed, as documented in previous studies [ 65 , 69 , 70 , 71 ]. Moreover, due to their nematic nature, of the mesophase, they exhibited the lowest order mesophase.…”
Section: Resultssupporting
confidence: 71%
“…The data revealed that the N–I transition entropy changes showed relatively lower values. The estimated entropy changes values are independent on alkoxy chain length [ 64 , 65 ]. Additionally, these results were agreement with previous reports [ 66 , 67 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on this parallel arrangement, we revealed the details of molecular aggregation in the Gyroid phase. 15 Considering the possible variety of alkyl-chain orientations and interdigitations, 15,45–47 we can imagine the molecular arrangement reasonably compatible with the reported chain-length dependence of the cell constant 18 (see ESI† for details), as shown in Fig. 5: the parallel alkyl chains with little interdigitation between the two junctions on a body diagonal (3 B and 3 Y ), and the bent chains directed to the six-membered circuit (S B ).…”
Section: Resultssupporting
confidence: 59%
“…The orientations of alkyl chains proposed above are literally on average relative to the body diagonal that coincides with the averaged molecular orientation there. 15,[45][46][47] The straight chains do not mean an all-trans state at all. Similarly, we do not claim anything concerning the tilt direction (around the body diagonal) of disordered alkyl chains, for which we need further studies having higher sensitivity even for dynamical correlation.…”
Section: Alkyl Packingmentioning
confidence: 99%